Conflicts Experienced And Preferred Conflict Management Style On The Self-Motivation Of Staff Nurses In Selected Private Hospitals In Laguna, Philippines: Basis For A Conflict Resolution Framework - Gibas Tisalona, Kathryn Joyce; Aliswag, Emerson Galang (Journal of Neonatal Surgery, 2025)
Background: Workplace conflicts among nurses significantly affect job satisfaction, teamwork, and patient care. This study investigated conflict experienced, preferred conflict management styles, and self-motivation among 254 staff nurses in private hospitals in Laguna, Philippines. It also proposed a framework to enhance a conflict resolution and self-motivation. Methods: Using a descriptive correlational design, date were collected through the Nursing Conflict Scale (NCS), Thomas Kilmann Conflict Mode Instrument (TKI), and the Self-Motivation Assessment Tool, grounded in Self-Determination Theory (SDT). Statistical analyses included Pearson correlation and regression (significance: p < 0.05). Results: Results revealed intergroup conflicts as most common highlighting coordination challenges. Nurses favored collaborative conflict management (mean = 3.13 ± 0.131) and least favored avoidance (mean = 2.86 ± 0.170). Self-motivation positively correlated with conflict frequency (r = 0.318, p < 0.001), while conflict experience negatively correlated with compromising and competing styles (r = 0.203, p = 0.001). Regression analysis indicated self-motivation explained 63.3% variance in conflict experienced and preferences for compromising and competing styles (R2 = 0.633, p < 0.001). Conclusion: Higher self-motivation encourages proactive conflict resolution and collaboration, though frequent conflicts may lead nurses to avoid confrontations. The study introduced the K.A.P.W.A. Staff Nurses Conflict Resolution Framework, offering practical strategies to enhance conflict management, motivation, and professional growth. Institutions should implement structured training, supportive leadership, and clear workplace policies to strengthen teamwork and patient care outcomes